Rekruttering af deltagere til online spørgeskemaundersøgelser om kriminelle aktiviteter - Thomas Friis Søgaard; Nina Tvede Korshøj; Vibeke Asmussen Frank (Nordisk Tidsskrift for Kriminalvidenskab)
English abstract Internet-mediated research methods are increasingly used to access hidden crime-involved populations such as drug users and drug dealers. Based on an online survey study of over 800 individuals engaged in illegal small-scale cannabis cultivation in Denmark, this article focuses on the online recruitment methods used to access this allegedly »hidden« population. In the article, we critically reflect about the concepts of »hidden-« and »hard to reach« populations, and argue that small-scale cannabis growers are best understood as a group that is »accessible when approached with the right means«. More specifically, we outline the challenges involved in recruiting participants for an online survey that focuses on their criminal activities, and we provide insights into the different recruitment- and trust-building strategies used in this process. While the thematic focus of the article is on small-scale cannabis cultivation, the methodological approaches and reflections are also relevant for online survey studies of other types of offences.